2017
DOI: 10.1155/2017/8156594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bioactive Compound of Aronia melanocarpa on Cardiovascular System in Experimental Hypertension

Abstract: Aronia melanocarpa has attracted scientific interest due to its dense contents of different polyphenols. We aimed to analyse effects of Aronia melanocarpa (AME) extract on blood pressure (BP), lipid peroxidation, cytokine level, total NOS activity in the left ventricle (LV), and aorta of L-NAME-induced hypertensive rats. 12-week-old male WKY rats were assigned to the control group and groups treated with AME extract (57.90 mg/kg/day), L-NAME (40 mg/kg/day), or combination of L-NAME (40 mg/kg/day) and AME (57.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 34 publications
1
31
1
Order By: Relevance
“…Pechánová et al [ 28 ] determined a negative correlation between endothelial NOS expression and activity: an increased expression resulted in an activity reduction in order to maintain a constant level of NO in the cardiovascular system. Cebova et al [ 39 ] showed that although the long-term NO inhibition with L-NAME in adult WKY inhibited the NOS activity in the TA, it had no impact on the NOS protein expression. Regarding these facts, we speculated that only partially inhibited acetylcholine-induced vasorelaxation in the TA could be a negative feedback response of the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…Pechánová et al [ 28 ] determined a negative correlation between endothelial NOS expression and activity: an increased expression resulted in an activity reduction in order to maintain a constant level of NO in the cardiovascular system. Cebova et al [ 39 ] showed that although the long-term NO inhibition with L-NAME in adult WKY inhibited the NOS activity in the TA, it had no impact on the NOS protein expression. Regarding these facts, we speculated that only partially inhibited acetylcholine-induced vasorelaxation in the TA could be a negative feedback response of the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…Speci cally, the polyphenols content of chokeberry is higher than those of other berries (blueberry, cranberry and lingonberry crops), which exhibits various physiological activities such as antioxidant, antiin ammatory, antidiabetic, anti-cardiovascular diseases and so on [20][21][22][23]. Based on abundant phenolic substances content and various physiological effects of chokeberry, the aim of our study was to evaluate the impact of the polyphenols extract from chokeberry (CBPs) on improvement obesity and associated lipid metabolism disorders in HFD-fed rats, as well as comprehensive investigating the role of the gut microbiota in mediating the effects of the CBPs on host metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…AM contains various phenolic compounds, including anthocyanins, phenolic acids, and flavonoids [10]. In vitro and in vivo studies suggested that the phenolic compounds contained in AM possess a wide range of beneficial health functions, including antioxidant [11] [12], anti-hyperlipidemic [13] [14], anti-diabetic [15] [16], hepatoprotective [17], cardioprotective [18] [19] [20], and gastroprotective [21] activities. Recent animal studies demonstrated that AM reduced diet-induced obesity [22] [23].…”
Section: Introductionmentioning
confidence: 99%